2018
DOI: 10.1016/j.transproceed.2018.03.015
|View full text |Cite|
|
Sign up to set email alerts
|

EPO Derivative ARA290 Attenuates Early Renal Allograft Injury in Rats by Targeting NF-κB Pathway

Abstract: ARA290 protects against early renal allograft injury in rats by reducing macrophage infiltration, improving renal morphology, inhibiting mRNA expression of inflammatory mediators, and weakening the binding affinity of NF-κB to DNA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Previous studies have shown high protective activity of erythropoietin in various experimental pathologies and in many pathological conditions [ 24 , 25 , 26 ]. However, the use of erythropoietin is limited due to the side effects such as erythrocytosis, increased thrombosis, hypertension, growth progression, and the formation of new tumors [ 17 , 24 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown high protective activity of erythropoietin in various experimental pathologies and in many pathological conditions [ 24 , 25 , 26 ]. However, the use of erythropoietin is limited due to the side effects such as erythrocytosis, increased thrombosis, hypertension, growth progression, and the formation of new tumors [ 17 , 24 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The signaling pathway after its activation begins with the phosphorylation of JAK2 [ 29 ]. In other tissues, the heterodimeric receptor (EPOR-βCR) is located, or it is also called the innate repair receptor (IRR) [ 24 , 27 , 30 , 31 ]. The start of the signaling pathway after its activation also begins with the phosphorylation of JAK2; then, the activation of different signaling pathways leads to the implementation of non-erythropoietic effects depending on the tissues [ 30 , 31 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ARA 290, an 11-amino acid linear nonhematopoietic peptide derived from the three dimensional structure of helix B of the erythropoietin (EPO), interacts selectively with the innate repair receptor (IRR) that arbitrates tissue protection [24,25]. Activation of the IRR by ARA290 commences a local multi antiin ammatory pathways, which inhibit death signal and up-regulate survival signals and subsequently blocks in ammation-induced apoptosis, stimulates tissue restorative functions and produces nitric oxide by endothelial cells and subsequently inhibiting obvious tissue damage [24,26,27]. Besides, activation of the IRR also stimulates tissue repair responses, including free radical scavenging [28].…”
Section: Introductionmentioning
confidence: 99%
“…The bone marrow megakaryocytes have a homodimeric receptor (EPOR/EPOR) (Lin et al 2017;Huang et al 2018). In other tissues, there is a heterodimeric receptor (EPOR-βCR), so-called the innate repair receptor (IRR) (Culver et al 2017;Lin et al 2017;Wu et al 2017;Yan et al 2018).…”
mentioning
confidence: 99%